The Application of Snowball Throwing Learning Model to Improve Learning Outcomes in Social Studies Subjects for Class VIII-A: The Application of Snowball Throwing Learning Model to Improve Learning Outcomes in Social Studies Subjects for Class VIII-A - Ahmad Haqiqi; Sahrul Romadhon (SOCIALE: Jurnal Internasional Kajian Sosial, 2026)
Learning outcomes are certain competencies or abilities achieved by students after participating in the teaching and learning process and include cognitive, affective, and psychomotor skills. Learning outcomes are related to changes in knowledge, understanding, attitudes and behavior in a person due to the learning they do. Changes caused by growth are not included in learning outcomes. This study aims to improve learning outcomes in Social Studies subjects in class VIII-A at MTsN 1 Pamekasan. The study used the Classroom Action Research (CAR) method with two cycles. The subjects of the study were 26 students. cycle 1 with an average value of 66.42 and a learning completion value of 38.46%, this shows good development when compared to before. it can be concluded that the objectives that the researcher had hoped to have achieved, namely to improve student learning outcomes in Social Studies subjects in the cognitive aspect using the snowball throwing learning model